2019
DOI: 10.3390/cancers11101416
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosyl-DNA Phosphodiesterase 1 and Topoisomerase I Activities as Predictive Indicators for Glioblastoma Susceptibility to Genotoxic Agents

Abstract: Glioblastoma (GBM) patients have an estimated survival of ~15 months with treatment, and the standard of care only modestly enhances patient survival. Identifying biomarkers representing vulnerabilities may allow for the selection of efficacious chemotherapy options to address personalized variations in GBM tumors. Irinotecan targets topoisomerase I (TOP1) by forming a ternary DNA–TOP1 cleavage complex (TOP1cc), inducing apoptosis. Tyrosyl-DNA phosphodiesterase 1 (TDP1) is a crucial repair enzyme that may redu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Tyrosyl-DNA phosphodiesterase 1/2 (TDP1/2) resolve Top-DNA complexes by liberating Top1 or Top2 (respectively TDP1 and TDP2) from the DNA after the degradation of the cleavage complexes. A combination of inhibitors such as the Top1 inhibitor irinotecan with a TDP1 inhibitor also improves the treatment of glioblastoma [293]. A higher response to irinotecan (Top1 inhibitor) is obtained in BRCA2-mutated cancer with acquired resistance to olaparib (PARP inhibitor) showing the downregulation of TDP1 [294].…”
Section: Topoisomerase Inhibitorsmentioning
confidence: 99%
“…Tyrosyl-DNA phosphodiesterase 1/2 (TDP1/2) resolve Top-DNA complexes by liberating Top1 or Top2 (respectively TDP1 and TDP2) from the DNA after the degradation of the cleavage complexes. A combination of inhibitors such as the Top1 inhibitor irinotecan with a TDP1 inhibitor also improves the treatment of glioblastoma [293]. A higher response to irinotecan (Top1 inhibitor) is obtained in BRCA2-mutated cancer with acquired resistance to olaparib (PARP inhibitor) showing the downregulation of TDP1 [294].…”
Section: Topoisomerase Inhibitorsmentioning
confidence: 99%
“…One of the DNA repair enzymes is tyrosyl-DNA-phosphodiesterase 1 (Tdp1), which is capable of cleaving different adducts from the DNA 3 -end restoring its integrity [9]. On the one hand, Tdp1 is overexpressed in some types of cancer, such as non-small lung cancer [10] and glioblastoma [11]. On the other hand, it has been shown that Tdp1 knockout mice and Tdp1-deficient cells are hypersensitive to Top1 inhibitors [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increased Tdp1 expression counteracts the cytotoxicity of CPTs [30,31], and is frequently observed in cancers resistant to CPT therapy [31][32][33]. Convincing evidence exists from preclinical studies that the ratio of Tdp1/Top1 activity influences cellular sensitivity to Top1 inhibitors [34,35], and that the suppression of Tdp1 activity leads to an increase in the sensitivity of tumor cells to CPTs [32,[36][37][38][39]. It is believed that targeted short-term treatment with a potent Tdp1 inhibitor will not lead to serious poisoning in normal cells.…”
Section: Introductionmentioning
confidence: 99%